2010
DOI: 10.1186/1471-2229-10-195
|View full text |Cite
|
Sign up to set email alerts
|

Mutant alleles of FAD2-1A and FAD2-1Bcombine to produce soybeans with the high oleic acid seed oil trait

Abstract: BackgroundThe alteration of fatty acid profiles in soybean [Glycine max (L.) Merr.] to improve soybean oil quality is an important and evolving theme in soybean research to meet nutritional needs and industrial criteria in the modern market. Soybean oil with elevated oleic acid is desirable because this monounsaturated fatty acid improves the nutrition and oxidative stability of the oil. Commodity soybean oil typically contains 20% oleic acid and the target for high oleic acid soybean oil is approximately 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
250
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(263 citation statements)
references
References 37 publications
6
250
1
6
Order By: Relevance
“…roztworu chemicznego lub promieniowania. Do mutacji należy wybierać takie odmiany, w których można skontrolować cechę wytwarzania kwasu oleinowego dzięki jednemu genowi bądź grupie genów dominujących [14,31,43]. Mutanty oraz ich krzyżówki wykazują wysoką odziedziczalność w zakresie zawartości kwasu oleinowego, w porównaniu z pozostałymi KT oraz stabilność środowi-skową.…”
Section: Metody Otrzymywania Roślin O Zmienionym Składzie Ktunclassified
See 2 more Smart Citations
“…roztworu chemicznego lub promieniowania. Do mutacji należy wybierać takie odmiany, w których można skontrolować cechę wytwarzania kwasu oleinowego dzięki jednemu genowi bądź grupie genów dominujących [14,31,43]. Mutanty oraz ich krzyżówki wykazują wysoką odziedziczalność w zakresie zawartości kwasu oleinowego, w porównaniu z pozostałymi KT oraz stabilność środowi-skową.…”
Section: Metody Otrzymywania Roślin O Zmienionym Składzie Ktunclassified
“…Rośliny oleiste, które najczęściej są poddawane takim zabiegom to: słonecznik, rzepak, soja, orzechy ziemne, kukurydza i len [31]. Wszystkie wymienione rośliny są uprawiane na skalę przemysłową, a ich nasiona -przetwarzane [37].…”
unclassified
See 1 more Smart Citation
“…Selection for breeding and genetic engineering approaches resulting in elevated oleic acid levels have been reported in many oilseed crops [96][97][98]. Conventional soybean lines with 80% oleic acid accompanied by a corresponding decrease in linoleic acid were obtained based on the contribution of only two genes (FAD2-1A and FAD2-1B) [99].…”
Section: Improvement Of Biodiesel Feedstocksmentioning
confidence: 99%
“…Different genetic backgrounds and genetic resources responsible for elevated oleic acid concentrations have been developed by several researchers (Wilson et al 1981;Rahman et al 1994;Burton et al 2006;Monteros et al 2008;Dierking and Bilyeu 2009;Hoshino et al 2010;Pham et al 2010;Pham et al 2011 groups independently reported that soybeans with ∼80% oleic acid could be developed by combining mutant alleles at the FAD2-1A locus (Glyma10g42470) with mutant alleles at the FAD2-1B locus (Glyma20g24530) (Hoshino et al 2010;Pham et al 2010;Pham et al 2011). In the recent past, several researchers have studied the effects of high-oleic acid traits, developed by combining mutant alleles at the FAD2-1A locus with mutant alleles at the FAD2-1B locus, on seed yield, and reported that the high-oleic acid phenotype has no negative effects on yield (Hoshino et al 2010;La et al 2014;Kim et al 2015).…”
Section: Introductionmentioning
confidence: 99%